Statistical Anxiety of Religious College Students: A Review of Reducing Factors of Statistical Anxiety - Deni Iriyadi; Yogi Damai Syaputra; Monalisa Monalisa (International Journal of Pedagogy and Teacher Education, 2024)
This research aims to determine the level of statistical anxiety among students from religious universities. Understanding this is crucial since knowledge of statistics is necessary for completing final assignments, while the students' backgrounds are generally from Islamic boarding schools. This research employs a mixed-method approach with an explanatory sequential design, prioritizing a quantitative approach followed by a qualitative approach. The respondents were students enrolled in statistics courses, totaling 479 participants. The sampling technique used multistage random sampling, starting with cluster random sampling, followed by purposive sampling. Anxiety levels were measured using the Statistics Anxiety Scale (SAS) instrument, consisting of 17 questions covering three aspects: worry, avoidance, and emotional aspects. The Mixed-Methods Sequential Explanatory Design involved gathering and analyzing quantitative data first, followed by qualitative data. Results indicated differences in statistical anxiety levels among non-exact students. Initially, 45% of students exhibited high anxiety levels, which decreased to 14%, while low anxiety levels increased from 27% to 49%. This suggests that learning processes requiring complex numeracy need appropriate interventions, such as using various tools (software) that significantly impact the learning process. Implementing a peer tutoring program can also boost self-confidence. Therefore, study program managers or lecturers must focus on enhancing students' self-confidence to reduce anxiety. Using suitable learning aids can make a significant difference..